Sistem Informasi Penggajian Karyawan pada UMKM “Makaroni Ira” - adminjftr adminjftr; Zakiya Muallifa Rahman (JERA : Journal of Engineering Research and Application, 2022)
An information system is a system that, apart from performing all the transaction processing is necessary for an organization, also provides information and processing support for management and decision-making functions. Every organization always needs systems to collect, process, store, review and distribute information. "Makaroni Ira" is a Small Business that does not yet have a payroll information system so that the payroll is still done manually, making it difficult for company managers and takes a long time to decide all the employee salaries. The way to solve the payroll problem in Makaroni Ira's business is to create an application that can automatically process the existing input data. The solution is to use the information system design method, then make the process and data modeling, then build the application